Understanding and doing successful research : data collection and analysis for the social sciences - Best, Shaun (Harlow : Pearson, 2012)
'Research Methods' is a guide to carrying out a research project. Each of the focused chapters introduces and explains an aspect of social research to readers who may have no experience or knowledge of this subject.
Includes bibliographical references and index.
Keywords: Social sciences -- Research -- Methodology